Formation of Bodies of Large and Small Mass - Iakubovskii E. G. (Actual problems of education fundamentalization)
Astronomers do not know the mechanism of formation of planets and stars, as well as the mechanism of formation of galaxies. It would seem that planets and stars should be evenly distributed throughout space, but they form into galaxies. Understanding and describing these problems requires a mechanism to function.
Keywords: fluctuations of large and small mass; correspondence between the masses of super-large masses and heavy elementary particles; the Navier-Stokes equation determining super-large masses; флуктуации большой и малой массы; соответствие масс сверхбольшой массы и тяжелых элементарных частиц; уравнение Навье-Стокса; определяющее сверхбольшие массы